Social and Regional Disparities in Utilization of Maternal and Child Healthcare Services in India: A Study of the Post-National Health Mission Period - Bango, Madhumita; Ghosh, Soumitra (Frontiers in Pediatrics, 2022)
Background India has enjoyed enhanced economic growth, but has fared poorly in human development indicators and health outcomes, over the last two decades. Significant health inequities and access to healthcare continue to exist and have widened within communities across states. This study examine the changes and disparities in maternal and child healthcare (MCH) among disadvantaged and advanced social groups in three states of India. Data and Methods Four rounds of National Family Health Survey data were used to measure infant mortality rate (IMR) and under-five mortality rate (U5MR) according to the social groups for the selected states. This study investigates the socio-economic inequities manifested into caste and class differentials and inequities in availability, utilization, and affordability of maternal and healthcare services. Descriptive statistics and the logistic regression model were used. Individual- and household-level covariates were employed to understand the differentials in healthcare utilization. Results The probability of not receiving full antenatal care (ANC) or full immunization for the children was highest among the Scheduled Caste/Scheduled Tribe (SC/ST) families, followed by economic class, mother's education and residence. Tamil Nadu showed the highest utilization of public health facilities, while Bihar was the poorest in terms of health outcomes and utilization of MCH care services even after the pre-National Health Mission (NHM) period. Bihar and West Bengal also showed private healthcare dependence. Conclusion This study detected the presence of significant caste/tribe differentials in the utilization of MCH care services in the selected states of India. Limited accessibility and unavailability of complete healthcare were the foremost reasons for the under-utilization of these services, especially for people from disadvantaged social groups. The result also suggested that it is perilous to confirm “Health for All” immediately. It will be the efficiency with which India addresses inequities in providing healthcare services and guarantees quality care of health services.